Characterizations of Some Composite Materials - El-Din Saleh, Hosam M.; Koller, Martin (IntechOpen, 2019)
Composite materials are materials made from two or more constituents with significantly different physical or chemical properties; when combined, a new material with characteristics different from the individual components is produced, while the individual components remain separate and distinct within the finished structure. The new composite material often displays many beneficial characteristics; in many cases, composites are stronger, of lower density, or less costly in comparison to established materials. Based on the classification of composites, we are already familiar with the fact that there exists a myriad of different types of these materials. It is a common saying that different types of composites differ in their performance. Yet, composites also have some characteristics in common. The proper material choice for an envisaged application is of outstanding importance and key in the development of a new product. Selecting the most suitable material determines the performance and characterization of the final product whether it will meet the designated function and performance requirements. The present book "Characterizations of some composite materials" contains eight selected chapters, starting with a general introductory chapter on composite materials, and covers different aspects in characterizing some composite materials. In this context, the present book is considered an appropriate way to communicate the advances in characterization of some composite materials to the scientific community. Chemists, scientists, and researchers from related areas, and undergraduates involved in materials issues and interested in approaches to improve the quality of life, as well as people from industry could find this book to be an inspiring and effective guide.